Understanding the Thermoelectric Transport Properties of Organic Semiconductors through the Perspective of Polarons - Venkateshvaran, Deepak; Cervantes., Mateo T.R; Spalek, Leszek J.; Hwang, Ki-Hwan; Pudzs, Kaspars; Rutkis, Martins; Schweicher, Guillaume; Padilla-Longoria, Pablo (American Association for the Advancement of Science, 2024)
Thermoelectric properties of organic semiconductors have been intensively studied over the last 15 years for their application in converting waste heat into electricity. Optimism in the field of organic thermoelectrics points at the possibility of achieving figures of merit (ZT) approaching or exceeding one. Despite tremendous research effort over the years, however, such market-competitive values of ZT have not been demonstrated. The efficiency of waste heat to electricity conversion using organic semiconductors depends on their transport physics. This physics is understood through the interrelationship between the electrical conductivity (σ), the Seebeck coefficient (S), and the thermal conductivity (κ). Several thermoelectric transport models were developed to explain the observed relationship between these coefficients in organic semiconductors. Most models predict the measured thermoelectric transport behavior within a limited range, either in the nondegenerate regime of low electrical conductivity or in the near-degenerate regime of high electrical conductivity. Here, we deploy a simple model based on hopping transport to explain the experimentally observed relationship between the electrical conductivity and the Seebeck coefficient in organic semiconductors. This hopping-based transport model spans a broad range of charge carrier densities encompassing both the nondegenerate regime and the near-degenerate regime. The model was originally used to identify polaronic transport in multifunctional conductive oxide-based materials and is shown here to be applicable to organic semiconductors. Our work spotlights an alternative explanation for recent experimental observations in organic thermoelectrics within a unified description. It documents factors that keep ZT ~ 1 elusive in single layers of organic semiconductors, despite their understood merits in thermoelectrics. Copyright © 2024 Deepak Venkateshvaran et al. This is an open-access publication Venkateshvaran D., Cervantes M.T.R., Spalek L.J., Hwang K.-H., Pudzs K., Rutkis M., Schweicher G., Padilla-Longoria P. Understanding the Thermoelectric Transport Properties of Organic Semiconductors through the Perspective of Polarons (2024) Advanced Devices and Instrumentation, 5, art. no. 0067, DOI: 10.34133/adi.0067.
D.V. acknowledges valuable discussions with D. Venkataraman (University of Massachusetts Amherst), Z. Aksamija (University of Utah), H. Tanaka (Nagoya University), and H. Sirringhaus (University of Cambridge) in the preparation of this manuscript. Funding: D.V. also acknowledges the Royal Society for funding in the form of a Royal Society University Research Fellowship (Royal Society Reference No. URF/R1/201590). G.S. is a Belgian National Fund for Scientific Research (FNRS) Research Associate. G.S. acknowledges financial support from the Francqui Foundation (Francqui Start-Up Grant) and thanks the FNRS for financial support through research project COHERENCE2 (no. F.4536.23). D.V. and G.S. acknowledge the Wiener-Anspach Foundation (FWA) for support of the ZT1 research project initiated in 2024. The ZT1 project aims to demonstrate ZT = 1 figure of merit in organic thermoelectric. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART²
Keywords: Research Subject Categories::NATURAL SCIENCES